The challenge of involving old patients with polypharmacy in their medication during hospitalization in a medical emergency department: An ethnographic study. - Pia Keinicke Fabricius; Ove Andersen; Karina Dahl Steffensen; Jeanette Wassar Kirk (PLoS ONE, 2021)
Background More than 70% of patients admitted to emergency departments (EDs) in Denmark are older patients with multimorbidity and polypharmacy vulnerable to adverse events and poor outcomes. Research suggests that patient involvement and shared decision-making (SDM) could optimize the treatment of older patients with polypharmacy. The patients become more aware of potential outcomes and, therefore, often tend to choose less medication. However, implementing SDM in clinical practice is challenging if it does not fit into existing workflows and healthcare systems. Aim The aim was to explore the determinants of patient involvement in decisions made in the ED about the patient's medication. Methods The design was a qualitative ethnographic study. We observed forty-eight multidisciplinary healthcare professionals in two medical EDs focusing on medication processes and patient involvement in medication. Based on field notes, we developed a semi-structured interview guide. We conducted 20 semi-structured interviews with healthcare professionals to elaborate on the findings. Data were analyzed with thematic analyses. Findings We found five themes (determinants) which affected patient involvement in decisions about medicine in the ED: 1) blurred roles among multidisciplinary healthcare professionals, 2) older patients with polypharmacy increase complexity, 3) time pressure, 4) faulty IT- systems, and 5) the medicine list as a missed enabler of patient involvement. Conclusion There are several barriers to patient involvement in decisions about medicine in the ED and some facilitators. A tailored medication conversation guide based on the SDM methodology combined with the patient's printed medicine list and well-functioning IT- systems can function as a boundary object, ensuring the treatment is optimized and aligned with the patient's preferences and goals.